Estación de carga solar para bicicletas y monopatín eléctricos de baja potencia para el I2TEC de la UNL - Cabrera Ordoñez, Edwin Segundo (2023)
Renewable energies have great potential in reducing environmental emissions due to vehicles that use petroleum as fuel. The sun, as an inexhaustible source of energy, produces a large amount of electricity by using photovoltaic systems, these systems are found in those places that are far from a power grid or where there is a great shortage of energy. This thesis provides information and data about a solar station using photovoltaic systems to recharge low power electric bicycles and scooters by using the necessary equipment and techniques in any photovoltaic system. The design of this station can be replicated globally, since it is aimed at those electric vehicles, as a means of sustainable mobility using clean energy, clean energy helps us to clean the air we breathe in the form of energy that transport vehicles can use. Keywords: Renewable Energy, Types of Energy, MACD, SFV, Load Controller, SFVA.